Assessing and forecasting groundwater development costs in Sub-Saharan Africa - Xenarios, Stefanos; Pavelic, Paul (African Journals Online, 2013)
Greater use of groundwater in Sub-Saharan Africa is a pre-requisite for improved human welfare; however, the costs associated with groundwater development are prohibitively high and poorly defined. This study identifies and disaggregates the costs of groundwater development in 11 Sub-Saharan African countries, while the cost factors that most strongly affect drilling expenditures are traced. Further, the institutional and technical constraints impeding groundwater development are also explored while a time-series analysis forecasts future drilling expenditures. The results indicate that mobilisation and demobilisation costs, together with well development costs, factors that are difficult to change, are most significantly affecting the total costs of drilling. Further, the nature of the hydrogeological formation (which is largely a site characteristic), along with the often-aged machinery (which can be controlled), are also major impediments to lowering the cost of drilling. All countries are forecasted to have a slight to considerable drilling cost decrease for the next decade which offers encouragement for future groundwater development. Greater attention to the individual cost factors and to forecasting analysis could help to design more coherent and consistent groundwater development policies in Sub-Saharan Africa.